An analysis of the U.P. High School science achievement test - Ysip, Librada M. 1922- (1964)
This study presents data on the validity, reliability, and norms of an achievement test in science developed for the fourth year students of the UP Preparatory School and UP High School.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Secondary).; University of the Philippines (Diliman). -- High School